Library Application Program at State Vocational High School X Bandung City - Sukma Hendrian (Politeknik Siber Cerdika Internasional, 2021)
The development of Information Technology began to receive a positive response from the public. Its development is not only welcomed and enjoyed by the business world and the government, but has also begun to penetrate the world of education because the integration of availability is increasingly important in supporting efforts to create the next generation of competitive nations. or being researched. The purpose of this research is to find out what are the effects of library program applications. Such information can be obtained from scientific books, research reports, scientific papers, theses and dissertations, laws and regulations, articles of association, yearbooks, encyclopedias and written sources both printed and electronic and the internet. information and data related to the need to complete the final project.